Advancing Green Economy: Case Studies from Indonesia, Ghana, and Strategies for Governance and Eco-Management - Ardhi, Fillah; Aditya, Farhan; Hwihanus (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2024)
This paper underscores the imperative of acknowledging the adverse impacts of economic development to foster sustainable economic growth. It advocates for the adoption of the green economic concept as a viable solution, emphasizing natural resource conservation. Employing discriminant analysis, the study assesses green economic development across income-classified countries, revealing the significance of environmental factors such as emissions and forest area. While the principles of a green economy gain traction globally, concerns linger among some nations about potential hindrances to development. Consequently, a clear methodology for green economy implementation is crucial, particularly in the context of governance. The research discusses prerequisites, basic principles, and modeling techniques for green economy implementation, employing the IDEF0 methodology. Using Ghana as a case study, SWOT analysis evaluates its green economy transformation efforts, highlighting strengths like geographical advantages and weaknesses such as weak institutions. Opportunities include international support, while threats encompass inadequate technology development and corruption. The study underscores the necessity for policymakers to leverage strengths and opportunities while addressing weaknesses and threats, emphasizing science and technology education to support green economy development. Furthermore, the paper explores the significance of eco-management in fostering a green economy, advocating for new scientific approaches to managerial decision-making. It delineates management technologies for eco-management, focusing on resource-oriented production and competitive strategy. The study underscores the importance of resource efficiency in economic and environmental aspects, offering practical recommendations for industrial waste reuse. Lastly, employing the nonlinear ARDL approach, the paper analyzes the asymmetric impact of renewable energy generation and clean energy prices on green economy stock prices. Results indicate significant negative impacts of renewable energy generation, with clean energy prices exhibiting both positive and negative effects. The study concludes by highlighting the dominance of negative shocks and the intricate relationship between renewable energy generation, clean energy prices, and green economy stock prices.